The Economics of Capital Regulation in Financial Conglomerates - Morrison, A (2003)
Provides and academic perspectives on the role of, and the justification for, financial regulation in the insurance industry. Considerations in capital regulation; Industry view that regulators should account for diversification effects at the holding company level; Framework for capital adequacy policy-making.